Pengaruh Motivasi Belajar dan Efikasi Diri Terhadap Kemandirian Belajar Siswa SMP Negeri 2 Ngantru Tulungagung Tahun Pelajaran 2024/2025 - Sukmilah, Lenita Putri; Hastuti, Maria Agatha Sri Widyanti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The purpose of this study was to determine: 1) The effect of learning motivation on learning independence, 2) The effect of self-efficacy on learning independence. Quantitative research type with multiple linear regression analysis. The population was 145 students with a sample of 106 students. Data collection techniques used a questionnaire. Partially, learning motivation affects learning independence, self-efficacy affects learning independence. Simultaneously, learning motivation and self-efficacy affect learning independence. The results showed that learning motivation had a tcount value> ttable, namely 7.957> 1.983 with a significance value of 0.000 <0.05, it can be concluded that there is a positive and significant effect of learning motivation on learning independence, self-efficacy has a tcount value> ttable, namely 3.456> 1.983 with a significance value of 0.001 <0.05, it can be concluded that there is a positive and significant effect of self-efficacy on learning independence. Simultaneously has a value of F count (69,739) > F table (3.94) with a significance value of 0.000 < 0.05. The results of the Adjusted R Square value of 56.7% are influenced by the variables of learning motivation (X1) and self-efficacy (X2), while the remaining 43.3% are influenced by other factors outside the variables of learning motivation (X1) and self-efficacy (X2).